Концепції підготовки майбутніх учителів у Польщі - Євтушенко, Наталія (НТУ "ХПІ", 2016)
Стаття присвячена розгляду актуальних питань підготовки майбутніх учителів у системі освіти Польщі. Описано головні концепції, на основі яких відбувається процес навчання та підготовки польських педагогів. Проаналізовано погляди науковців щодо вдосконалення професійної підготовки майбутніх учителів, визначено подальші перспективи вивчення досліджуваної проблеми.

The paper deals with the actual problems of future teacher training in the educational system of Poland. The author describes the main concepts which the process of education and training of Polish teachers has been based on. The researchers’ views on the improvement of professional training of future teachers are analyzed; the perspectives of further investigating of the problem are defined.
The concepts for training of future teachers in Poland
Keywords: система освіти Польщі; педагогічна освіта; польський учитель; професійна підготовка; освітні трансформації; teacher; educational system of Poland; pedagogical education